EFEK MODERASI MOTIVASI BELAJAR PENGARUH ACADEMIC HARDINESS DAN LINGKUNGAN KELUARGA PADA HASIL BELAJAR - Wedi Pratama (FKIP Unswagati, 2022)
AbstractThis research is motivated by the existence of problems in student learning outcomes at the 2018 Faculty of Economics and Business Education which are still low. The purpose of this research is to find out and analyze the influence of academic hardiness and family environment on learning outcomes with the moderating variable of learning motivation. The method used in this study is an explanatory survey research with data collection techniques through questionnaires. The population of this research is students of the Faculty of Economics and Business Education Class of 2018 as many as 615 students while the sample is 243 students. The data that has been collected is then analyzed using multiple linear regression data analysis techniques with Moderate Regression Analysis (MRA). The results showed that learning outcomes and academic hardiness were in the medium category, while the family environment and learning motivation were in the high category. In addition, the results of this study show 1) Academic Hardiness and Family Environment affect learning outcomes, 2) Learning motivation moderates the influence of academic hardiness on learning outcomes, 3) Learning motivation moderates the influence of family environment on learning outcomes.Keyword: Academic Hardiness, Family Environment, Learning Motivation, Learning Outcomes